A cytokine screen using CRISPR-Cas9 knock-in reporter pig iPS cells reveals that Activin A regulates NANOG - Junjun Xu (Stem Cell Research & Therapy, 2020)
Abstract Background NANOG functions as the gateway for the generation of pluripotent stem cells (PSCs) in mice and humans. NANOG is a transcription factor highly expressed in pig pre-implantation embryos, indicating that it is a conserved pluripotency-associated factor. However, pig NANOG reporter PSCs have yet to be established, and the regulation of pluripotency by NANOG is not fully understood in this animal. Methods In this study, pig NANOG tdTomato knock-in reporter positive PC-iPS cells were established using CRISPR/Cas9. The resulting cell line was treated with several cytokines and their corresponding inhibitors to identify pathways that regulate NANOG expression. The pathways examined were LIF (leukemia inhibitory factor)/IL6 (interleukin 6)-STAT3, FGF (fibroblast growth factor)/ERK, IGF1 (insulin-like growth factor 1)/PIP3 (phosphoinositide 3-kinase)-AKT, Activin A/SMAD, and BMP4 (bone morphogenetic proteins)/SMAD. Results Our experiments showed that the Activin A/SMAD pathway is directly associated with activation of NANOG expression in the pig, as is also the case in mice and humans. Activin A directly regulates the expression of pig NANOG via SMAD2/3; inhibition of this pathway by SB431542 resulted in inhibition of NANOG expression. Conclusions Our results show that Activin A plays an important regulatory role in NANOG-mediated pluripotency in pig iPS cells. Activin A treatment may be therefore an effective method for de novo derivation of authentic embryonic stem cells (ESCs) from pig pre-implantation embryos.